Total Consumption: The Meaning of Exchange in the Tanimbar Archipelago, Eastern Indonesia - Howes, David (Anthropologica, 2022)
This article describes the forms and meaning of "total prestation" in the context of Tanimbarese society in Eastern Indonesia. With respect to form, it is shown that exchange takes place along two axes, one affinal, the other fraternal. Relations between affinal alliance partners are hierarchical and asymmetrical in character, while those between brotherhood alliance partners are egalitarian and symmetrical. With regard to meaning, it is demonstrated that the ritual idiom in which exchange is expressed is replete with metaphors of predation: a creditor stands to his debtor as a predator stands to his prey. This all-consuming logic can be shown to structure all aspects of Tanimbarese experience, including death, which is regarded as the moment at which God, the supreme creditor, "consumes" a person's soul in payment for all of his or her outstanding debts.